Applying behavioural science to the annual electoral canvass in England: Evidence from a large-scale randomised controlled trial. (April 2021) - Sweeney, Martin; John, Peter; Sanders, Michael; Wright, Hazel; Makinson, Lucy
Abstract: Local authorities in Great Britain are required to ensure that their electoral registers are as accurate and complete as possible. To this end, Household Enquiry Forms (HEFs) are mailed to all properties annually to collect updated details from residents, and any eligible unregistered residents will subsequently be invited to register to vote. Unfortunately, HEF nonresponse is pervasive and costly. Using insights from behavioural science, we modified letters and envelopes posted to households as part of the annual canvass, and evaluated their effects using a randomised controlled trial across two local authorities in England (N=226, 528 properties). We find that modified materials – particularly redesigned envelopes – significantly increase initial response rates and savings. However, we find no effects on voter registration. While certain behavioural interventions can improve the efficiency of the annual canvass, other approaches or interventions may be needed to increase voter registration rates and update voter information.